When a Translator Joins the Revolution: A Paratextual Analysis of Manuel García de Sena’s La independencia - Núñez, Gabriel (TTR)

(untitled) (Association canadienne de traductologie, 2014)
During the complex period of Latin American independence, new states began to emerge and new ideas were implemented. Some of these ideas were made available in part due to the efforts of translators in the United States. Among them was Manuel García de Sena, a Venezuelan translator who published translations of North American texts. His translations enjoyed a prompt distribution. One of them became a vehicle that facilitated legal transplants from the United States to the new republics. While much has been lost to history regarding the details of the printing of this translation, its paratextual apparatus provides insights that help modern readers understand some things regarding the people involved, their ideas, and the times they lived in. By analyzing the title, the dedications, and the notes, we can see the translation’s intended function in changing the culture repertoire. In essence, the paratext allows us to see what this translator did as he joined the revolution.